Consumer protection and financial stability In the new spanish credit regulation real estate - Aránzazu Calzadilla, María Aránzazu (2020)
This essay, first, presents an analysis of the Norm 2014/17, which regulates consumer credit agreements regarding real estate. The Norm, in short, aims at ensuring that the Member States of the European Union have internal rules and regulations that provides for real, efficient, and a guaranteed protection for consumers, while, simultaneously, promoting the creation of a European mortgage market. Secondly, this essay discusses the legal regime established by the new law, that transposes the Norm onto the Spanish legal system.